Change in left atrial function and volume predicts heart failure with preserved and reduced ejection fraction: the multi-ethnic study of atherosclerosis. (3rd October 2022) - Lim, D; Varadarajan, V; Quinaglia, T; Pezel, T; Wu, C; Noda, C; Heckbert, S; Bluemke, D; Ambale-Venkatesh, B; Lima, J
Abstract: Aims: This study used cardiac magnetic resonance (CMR) imaging to investigate the relationship between longitudinal change in left atrial (LA) function and incident heart failure (HF), in a multi-ethnic population free of known cardiovascular disease at baseline. Methods and results: In the Multi-Ethnic Study of Atherosclerosis (MESA), 2470 participants (60±9 years, 47% males), free at baseline of clinically recognized cardiovascular disease, had LA volume and function assessed with CMR imaging at baseline (2000–02) and 9.4±0.6 years later. Seventy three (3%) participants developed incident HF over 7.1±2.1 years; of these, 39 participants had preserved ejection fraction (HFpEF) and 34 participants had reduced ejection fraction (HFrEF). An annual decrease of 1-SD unit in peak LA strain (ΔLASmax) was most strongly associated with the risk of HFpEF (subdistribution HR=2.56, 95% confidence interval (CI) [1.34–4.90], P=0.004) and improved model reclassification and discrimination in predicting HFpEF (c-statistic=0.84, 95% CI [0.79–0.90]; NRI=0.34, P=0.01; IDI=0.02, P=0.02; x2=4.25, P=0.89) adjusting for event-specific risk factors and baseline LA parameters. An annual decrease of 1ml/m 2 of pre-atrial LA volume index (ΔLAVipreA) was most strongly associated with the risk of HFrEF (subdistribution HR=1.88, 95% CI [1.44–2.45], P<0.001) and improved model reclassification and discrimination in predicting HFrEF (c-statistic=0.81, 95% CI (0.72–0.90); NRI=0.31, P=0.03; IDI=0.01, P=0.50; x2=15.4, P=0.08), adjusting for event-specific risk factors and baseline LA measures (Table 1). Conclusion: In this multi-ethnic population free of clinical cardiovascular disease at baseline, ΔLASmax and ΔLAVipreA were associated with, and incrementally predictive of HFpEF and HFrEF respectively, after adjusting for event-specific risk factors and baseline LA measures. Disclaimer: The views expressed in this abstract are those of the authors and do not necessarily represent the views of the National Heart, Lung, and Blood Institute; the National Institutes of Health; or the U.S. Department of Health and Human Services. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): National Heart, Lung and Blood InstituteNational Center for Advancing Translational Sciences